A Context‐Dependent View on the Linguistic Interdependence Hypothesis: Language Use and SES as Potential Moderators. Issue 2 (June 2015) - Prevoo, Mariëlle J.L.; Malda, Maike; Emmen, Rosanneke A.G.; Yeniad, Nihal; Mesman, Judi
<x xml:space="preserve">Abstract</x> The linguistic interdependence hypothesis states that the development of skills in a second language (L2) partly depends on the skill level in the first language (L1). It has been suggested that the theory lacked attention for differential interdependence. In this study we test what we call the hypothesis of context‐dependent linguistic interdependence. In order to do so, we examined child language use and socioeconomic status as two moderators in the relation between L1 vocabulary and L2 vocabulary growth in a sample of 104 5‐ and 6‐year‐old bilingual children with a Turkish background in the Netherlands. Relative child language use moderated the relation between L1 vocabulary and L2 vocabulary growth. Positive transfer was only present for children who used L1 more than L2. Socioeconomic status (SES) predicted growth in Dutch vocabulary but was not a moderator of linguistic interdependence, indicating that linguistic interdependence effects are similar across SES groups. The findings suggest the linguistic interdependence hypothesis is context‐dependent and only valid under circumstances of more L1 use.